Isolated cerebral mucormycosis masquerading as a tumor in an immunocompetent patient - Smita Chandra; Shubhi Sharma; Ruchir Vats; Sanjeev Pandey (University of São Paulo, 2021)
Mucormycosis is an opportunistic fungal disease that commonly presents as cutaneous or rhinocerebral infections associated with immunocompromised states. It may exceptionally present as isolated involvement of the brain with a varied clinical presentation, which may be difficult to diagnose early, leading to increased mortality. Herein, we report the case of a 42-yearold immunocompetent female with left-sided limb weakness and a history of recurrent vomiting and headache for the last two years. Clinically, glioma was suspected, but histopathological examination revealed a few broad aseptate fungal hyphae. As no other organ was involved, the diagnosis of isolated cerebral mucormycosis was rendered. Reporting this case, we show an unusual presentation of a central nervous system mucormycosis masquerading a tumor in an immunocompetent patient. The case also highlights the importance of a careful histopathological examination to avoid missing the presence of occasional fungal hyphae. Ideally, recognition of fungal hyphae in the brain, during intraoperative consultation, can prompt brain tissue culture for definitive diagnosis and early empirical antifungal therapy, Mucormycosismay prove life-saving.